2007
DOI: 10.1007/s00125-007-0814-x
|View full text |Cite
|
Sign up to set email alerts
|

Increased nicotinamide nucleotide transhydrogenase levels predispose to insulin hypersecretion in a mouse strain susceptible to diabetes

Abstract: Aims/hypothesis Insulin hypersecretion may be an independent predictor of progression to type 2 diabetes. Identifying genes affecting insulin hypersecretion are important in understanding disease progression. We have previously shown that diabetes-susceptible DBA/2 mice congenitally display high insulin secretion. We studied this model to map and identify the gene(s) responsible for this trait. Methods Intravenous glucose tolerance tests followed by a genome-wide scan were performed on 171 (C57BL/6 × DBA/2) × … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
77
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 73 publications
(81 citation statements)
references
References 46 publications
4
77
0
Order By: Relevance
“…We found that in contrast to C57BL/6 mice, which have a genetic disruption in Nnt, and the 129T2 mice, which show low levels of expression, the diabetes-susceptible DBA/2 mice show a fivefold overexpression of this gene, which encodes the mitochondrial proton pump known as nicotinamide nucleotide transhydrogenase. Insulin secretion was elevated in DBA/2 mice relative to that in C57BL/6 and 129T2 mice [18][19][20] Interestingly, we found that other strains of mice (BALB/c, FVB/N) that have previously been shown to be susceptible to diabetes when subjected to genetically induced obesity and insulin resistance also displayed increased NNT activity. We suggest that reduced NNT levels in the C57BL/6 and 129T2 strains result in lowered insulin secretion and mild glucose intolerance [21], and that protection against the development of diabetes in response to genetically induced obesity and insulin resistance may paradoxically be due to a reduced ability of the beta cell to secrete insulin.…”
Section: Ermentioning
confidence: 54%
“…We found that in contrast to C57BL/6 mice, which have a genetic disruption in Nnt, and the 129T2 mice, which show low levels of expression, the diabetes-susceptible DBA/2 mice show a fivefold overexpression of this gene, which encodes the mitochondrial proton pump known as nicotinamide nucleotide transhydrogenase. Insulin secretion was elevated in DBA/2 mice relative to that in C57BL/6 and 129T2 mice [18][19][20] Interestingly, we found that other strains of mice (BALB/c, FVB/N) that have previously been shown to be susceptible to diabetes when subjected to genetically induced obesity and insulin resistance also displayed increased NNT activity. We suggest that reduced NNT levels in the C57BL/6 and 129T2 strains result in lowered insulin secretion and mild glucose intolerance [21], and that protection against the development of diabetes in response to genetically induced obesity and insulin resistance may paradoxically be due to a reduced ability of the beta cell to secrete insulin.…”
Section: Ermentioning
confidence: 54%
“…Of the genes associated with HbA1c levels, 70 were also associated with in vitro insulin secretion in human islets, further highlighting their role in glucose metabolism (Database S1). Of particular interest are the genes whose expression is associated with lower HbA1c levels and higher insulin secretion, such as RAS guanyl releasing protein 1 (RASGRP1) (6), transcription factor RFX3 (21), and nicotinamide nucleotide transhydrogenase (NNT) (22), all of which have been suggested to regulate insulin secretion (SI Appendix, Figs. S5-S7).…”
Section: Significancementioning
confidence: 99%
“…Islets were prepared for cDNA synthesis and subsequent mRNA analysis using the method as previously described (Aston-Mourney et al 2007). Total RNA (2 mg) was reverse transcribed using the Promega Reverse Transcription System kit with random primers (Promega Corporation) and any contaminating DNA removed by treatment with DNaseI (RNase-free; Ambion).…”
Section: Islet Isolation and Cdna Preparationmentioning
confidence: 99%